Knowledge utilization process in highway construction projects - Alashwal, A.M.; Abdul-Rahman, H.; Radzi, J. (American Society of Civil Engineers, 2016)
The purpose of this paper is to determine knowledge utilization process and its influence on the performance of construction projects. Two cases of highway projects in Malaysia were used to develop a knowledge utilization model for managing time-related issues (i.e., factors causing project delay). The selected projects were similar in terms of size and scope, but the first project suffered from delay, while the second project was completed ahead of schedule. The findings traced the influence of knowledge utilization processes on project performance. The developed model was comprised of knowledge acquisition; knowledge conversion (knowledge sharing, creation, and integration); and new knowledge utilization. Also, the roles of three factors, namely, competence, teamwork, and time pressure, were highlighted in this model. This study shows knowledge utilization process while developing new solutions or making decisions about issues in the site and other daily problems that the project team is facing in road construction projects. The study emphasizes the significance of knowledge utilization to overcome time-related issues and enhance project performance.